Influence of soil texture in the recovery of Toxocara canis eggs by a flotation method - Nunes, Caris Maroni [UNESP]; Sinhorini, Idércio Luis; Ogassawara, Saemi (Elsevier B.V., 1994)
In epidemiological surveys, the evaluation of soil contamination by Toxocara canis eggs requires a quick and easy method for the isolation of parasite eggs from soil samples. The efficiency of flotation methods is influenced by sample size, soil texture, degree of soil contamination, pretreatment, flotation solutions and time of flotation. This investigation was designed to evaluate the influence of soil texture in the recovery of T. canis eggs with the centrifugal flotation technique of Dada (Dada, B.J.O., 1979. A new technique for the recovery of Toxocara eggs from soil. J. Helminthol., 53: 141-144). Four types of soil (clay silt, sandy, silty clay and sand) were artificially contaminated with T. canis eggs (200 eggs per gram). Zinc sulphate (specific gravity 1.20) and sodium dichromate (specific gravity 1.35) were used as flotation solutions. Twenty replicated examinations were performed for each type of soil and flotation solution. There was a statistically significant difference in the results depending on soil type. The highest recovery percentages were observed in soils rich in sand (62.5% for sand and 38.0% for sandy soil). Differences were also observed with different flotation solutions. Sodium dichromate solution was more efficient for recovering T. canis eggs, regardless of the soil texture. © 1994.
Keywords: Egg isolation; Epidemiology-Nematoda; Toxocara canis; Animal experiment; Brazil; Controlled study; Nonhuman; Parasite isolation; Sampling; Soil pollution; Toxocara canis; Toxocariasis; Worm egg; Analysis of Variance; Animal; Dogs; Epidemiologic Methods; Feces; Female; Ovum; Parasite Egg Count; Soil; Toxocariasis; Animalia; Canis; Nematoda; Toxocara